ANALISIS FAKTOR-FAKTOR PERILAKU KONSUMEN DALAM PEMBELIAN BIBIT JERUK MANIS (Citrus sinensis) DI DESA CINGKES - Posman Hp Marpaung (Universitas Pembangunan Panca Budi, 2018)
This study aims to investigate the characteristics of citrus seedlings Village Cingkes consumer, knowing the consumer perception of the marketing mix orange seed Cingkes village, and analyzes the factors that influence consumer purchasing decisions citrus seedlings Cingkes village. Area of ​​research conducted in the village of Cingkes Simalungun by determining the location of the research done purposively. Data used in this study are primary data. Samples were examined as many as 115 respondents. The number of variables studied as many as 25 variables, but only 19 valid variable. Data were processed using factor analysis was 19 variable because it has the MSA is above 0.5. Data obtained from respondents was processed using SPSS 17.0. Results showed that the characteristics of most of the respondents were male (71.3%), the age group of 20-79 years, the age of most respondents was 30-39 years (33%), with primary school up to undergraduate education, most are high school education (60.9%), with revenues Rp1,000,000 - 44,900,000. Most revenue is Rp 1,000,000 - 4,900,000 (68.7%). According to consumer product factor, factor prices, factor distribution, and promotion of citrus seedlings factor Cingkes village is very important and greatly affect the purchase of citrus seedlings Cingkes village, with 50% of respondents chose agree and strongly agree. The results of factor analysis showed that the results of the 19 variables that influence the purchase of citrus seedlings Village Cingkes form 7 factors. The factor is the price factor with variance value 20,064%, 11,231% social factors, with 9,837% distribution factor, promotion factor by 7,768% to 6,232% psychological factors, factors products by 5,769% and 5,645% of individuals with factor.